RESEARCH TRENDS IN PEER FEEDBACK IMPLEMENTATION IN EFL WRITING CLASSES - Kurnia Wulandari (Universitas Negeri Yogyakarta, 2025)
This systematic review aimed to present a systematic summary of the trends in the implementation of peer feedback, particularly in teaching writing skills in the EFL context. Research articles were collected from two different databases, namely Scopus and Web of Science. After being reviewed based on selected inclusion and exclusion criteria, 50 out of 162 collected articles were then further examined. The present study shows how peer feedback implementation is discussed in research articles published from 2022 to 2024. The majority of studies were conducted in 2022, most of the reviewed studies were developed based on the quantitative research design, and most of the feedback was delivered in direct face-to-face interaction.